The Influence of Tiktok Videos in Increasing Students’ Pronunciation Ability - Risa Safila (Journal of English for Academic and Specific Purposes (JEASP), 2023)
This study intended to show the effect of TikTok videos on students’ pronunciation skills . A quasi-experimental study design was used in this study. Students from MAN 2 Probolinggo participated in this study, 20 students consist as an experimental class and consist of 20 students as a control class. The results of this study showed a significant difference between students using TikTok videos as media learning and those using traditional strategies. Post-test results revealed that there was a significant effect of post-treatment on experimental class. Independent test results show that TikTok videos have a significant impact on students' pronunciation skills. However, the mean pretest scores of the experimental class are higher than  the control class. It can be concluded that TikTok videos have a positive effect on students' pronunciation ability and are accepted as an effective learning medium to improve students' pronunciation ability.